TEACHER CHALLENGES AND STRATEGIES IN MULTICULTURAL CLASS LEARNING AT MUHAMMADIYAH KUPANG HIGH SCHOOL - Muhajir Musa (CV. ADIBA AISHA AMIRA, 2025)
Learning in multicultural classes presents its own challenges for teachers, especially in managing students' cultural, ethnic and religious diversity. This research aims to analyze the challenges faced by teachers and the strategies implemented in multicultural classroom learning at Muhammadiyah High School Kupang. This research uses a qualitative approach with a case study method. Data was collected through in- depth interviews with teachers, classroom observations, and analysis of documentation related to policies and learning strategies. The research results show that the main challenges faced by teachers include differences in student learning styles, language barriers, and the potential for stereotypes and social conflict. To overcome this challenge, teachers apply various strategies, such as the use of inclusive learning methods, adaptive communication approaches, and character education based on tolerance and cooperation. Evaluation of the effectiveness of the strategy shows that this approach helps increase student interaction, build a harmonious learning environment, and strengthen their academic understanding. This research emphasizes the importance of support from schools in the form of teacher training and provision of resources to support multicultural learning. With the right strategy and adequate support, multicultural education can be an effective means of building an inclusive and tolerant learning environment.